IMMIGRATION PROCESSES IN THE MODERN GEOPOLITICAL SITUATION EXPECTED CHANGES IN THE FIELD OF LAW - Mukhammad, Khakberdiev (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article examines the anticipated changes in immigration processes as a result of ongoing military conflicts in Ukraine and Middle East. By analyzing recent developments in immigration law in the European Union (EU) and the United States (US), the article explores how these geopolitical crises influence immigration policies. The study includes statistical data, legal reforms, and policy responses, offering insights into future changes in the field of immigration law.